STUDI TENTANG EKSISTENSI BATAGAK GALA MASYARAKAT MINANGKABAU PADA ERA MODERNISASI DI KAMPUNG OLO KECAMATAN NANGGALO KOTA PADANG SUMATERA BARAT - REZA AYU REZA AYU TASBAL; Hambali; Jumili Arianto (JURNAL ILMU BUDAYA, 2022)
one of which is giving a title to the groom which is called the "Batagak gala" tradition. The formulation of the problem in this research is how is the existence of the "Batagak gala" tradition of Minangkabau society in the modernization era. The purpose of the study was to find out how the existence of the "batagak gala" tradition of the Minangkabau community in the modernization era in Olo Village, Nanggalo District, Padang City, West Sumatra. The data analysis technique in this study used a qualitative method with an ethnographic study approach. The results in this study explain that the "Batagak gala marapulai" tradition has undergone changes, including: the implementation time is not limited anymore, the place of implementation where the "Batagak gala" tradition